Caveolin-1 Variant Is Associated With the Metabolic Syndrome in Kuwaiti Children - Nizam, Rasheeba; Al-Ozairi, Ebaa; Goodson, Jo Max; Melhem, Motesam; Davidsson, Lena; Alkhandari, Hessa; Al Madhoun, Ashraf; Shamsah, Sara; Qaddoumi, Malak; Alghanim, Ghazi; Alhasawi, Nouf; Abu-Farha, Mohamed; et al. (Frontiers in Genetics, 2018)
Caveolin-1 (CAV1) variants have been suggested to be associated with obesity and related metabolic disorders, but information based on human studies is limited. In the present study, we aimed to investigate the potential association between the CAV1 rs1997623 C/A variant and metabolic syndrome (MetS) in Kuwaiti children. DNA from saliva samples collected from 1313 Kuwaiti children (mean age: 12 years) were genotyped using the TaqMan SNP genotyping assay. The classification of MetS was based on the presence/absence of four indicators; 1) central obesity, 2) elevated systolic or diastolic blood pressure, 3) low salivary high-density lipoprotein cholesterol (HDLC) and 4) high salivary glucose. In this study, children with MetS scored >3, children in the intermediate metabolic group scored 1 or 2 and children without MetS scored 0. About one-third of the children were obese. A total of 246 children (18.7%) were classified as having MetS; 834 children (63.5%) were in the intermediate metabolic group, and 233 children (17.7%) had no indication of MetS. Obesity was highly prevalent in the MetS group (91.9%) while 26.8% of children were obese in the intermediate metabolic group. None of the children were obese in the group without MetS. Analysis of the CAV1 rs1997623 variant revealed a significant association of the A-allele (p = 0.01, Odds Ratio (OR) = 1.66) and the heterozygous CA-genotype (p = 0.005, OR = 1.88) with MetS. Consistently, the A-allele (p = 0.002, OR = 1.71) and CA-genotype (p = 0.005, OR = 1.70) also showed significant association with the intermediate metabolic group. Furthermore, the A-allele (p = 0.01, OR = 1.33) and the CA-genotype (p = 0.008, OR = 1.55) were associated with low levels of saliva HDLC. Individuals who were heterozygous or homozygous for the variant (CA/AA) showed significantly lower levels of high HDLC compared to those harboring the CC-genotype (p = 0.023). Our study revealed a novel association of the CAV1 rs1997623 variant with the MetS and with low saliva HDLC levels in young Kuwaiti children and indicated the need for further in-depth studies to unravel the role of CAV1 gene in the genetic etiology of metabolic syndrome.